2020
DOI: 10.1371/journal.pone.0231835
|View full text |Cite
|
Sign up to set email alerts
|

A novel 20-gene prognostic score in pancreatic adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is among the most lethal cancers. Known risk factors for this disease are currently insufficient in predicting mortality. In order to better prognosticate patients with PDAC, we identified 20 genes by utilizing publically available high-throughput transcriptomic data from GEO, TCGA and ICGC which are associated with overall survival and event-free survival. A score generated based on the expression matrix of these genes was validated in two independent cohorts. We find t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…To better prognosticate patients with PDAC, researchers have established a 20‐gene score by utilizing publicly available high‐throughput transcriptomic data from GEO, TCGA and ICGC which have also reported on OS data. This 20‐gene pancreatic cancer prognostic score could define not only prognostic and biological subgroups, but predicted their responses to targeted therapy 33 . However, these risk scores did not focus on genes relating to glucose metabolism in PDAC, and the prediction efficiency was relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…To better prognosticate patients with PDAC, researchers have established a 20‐gene score by utilizing publicly available high‐throughput transcriptomic data from GEO, TCGA and ICGC which have also reported on OS data. This 20‐gene pancreatic cancer prognostic score could define not only prognostic and biological subgroups, but predicted their responses to targeted therapy 33 . However, these risk scores did not focus on genes relating to glucose metabolism in PDAC, and the prediction efficiency was relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…For comparison with our model, we selected two prognostic risk models: 20 gene signatures [ 21 ] and 36 gene signatures [ 24 ]. Survival analysis indicated that the PAAD prognosis of the high-risk score and low-risk score groups was different except for the 20-gene signature (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The prognostic value of various gene expression profiles has been studied in pancreatic cancer over the past decade. For example, Demirkol Canlı S and collaborators identified a gene signature composed of 20 prognostic genes (PPS20), indicating overall survival and event-free survival of pancreatic cancer [39]. Wolfe AR et al developed a 4-miRNA molecular signature that is associated with risk of local-regional recurrence and overall survival after pancreatic cancer resection [40].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Demirkol Canli et al . [ 39 ] identified a gene signature composed of 20 prognostic genes (PPS20), indicating OS and event‐free survival of pancreatic cancer. Wolfe et al .…”
Section: Discussionmentioning
confidence: 99%